Opter pour un accord à l’amiable (ṣulḥ) à Damas au xviiie siècle - Brigitte Marino (Revue des Mondes Musulmans et de la Méditerranée)
This article reflects the study of sixty legal acts recorded in Damascus court registers over two decades during the Ottoman period (1138-1159/1725-1746). Various cases resolved by mutual consent (ṣulḥ) allowed the author to examine the role of local and imperial institutions that intervened before the litigants had agreed on an amicable settlement. The article then identifies the crucial moment when a legal procedure moved toward amicable settlement and an end to a dispute. Finally, we study the outcome of these agreements, and how some litigants attempted to repudiate them. In a lawsuit, the amicable settlement option was usually chosen when a plaintiff could not produce evidence and the defendant was not bound by oath. Such agreements were concluded outside the courtroom, often as a result of mediators who were able to establish financial compensation. These agreements were then recorded by legal authorities.